EFEK GENDER SEBAGAI VARIABEL PEMODERASI PADA PENGARUH LITERASI KEUANGAN DAN GAYA HIDUP TERHADAP PENGELOLAAN KEUANGAN - Kathleen Asyera Risakotta (Jurnal Akun Nabelo: Jurnal Akuntansi Netral, Akuntabel, Objektif, 2023)
This study aims to determine the moderating effect of gender on the effect of financial literacy and lifestyle on financial management. This research was conducted with quantitative methodes. The population used in the study were accounting students amounted to 800 students with a sample of 132 respondent.  Sampling technique using random sampling. Primary data in the form of a questionnaire used in this study. This study uses the Moderated Regression Analysis (MRA). The results showed that financial literacy influences on financial management. Lifestyle influences on financial management. Gender has no effect on financial management. Gender is not a moderation in the relationship between financial literacy, lifestyle and financial management.